2011
DOI: 10.1038/sc.2011.104
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of upper limb robotic rehabilitation in a subacute cervical spinal cord injury population

Abstract: Study design: Multi-center pilot study. Objectives: To investigate the use of an upper limb robotic rehabilitation device (Armeo Spring, Hocoma AG, Switzerland) in a subacute cervical spinal cord injury (SCI) population. Setting: Two Canadian inpatient rehabilitation centers. Methods: Twelve subjects (motor level C4-C6, ASIA Impairment Scale A-D) completed the training, which consisted of 16.1 ± 4.6 sessions over 5.2±1.4 weeks. Two types of outcomes were recorded: (1) feasibility of incorporating the device in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 20 publications
3
99
0
Order By: Relevance
“…Although the degree of motor function recovery after stroke is strongly related to the site and severity of the lesion, the recovery process may be stimulated and molded by rehabilitation programs using various techniques and exercises designed to promote motor relearning (Stein et al, 2007;Oujamaa et al, 2009). However, because of the limited success of traditional rehabilitation programs in restoring upper extremity function after stroke, researchers have been searching for other solutions, including ones integrating advanced technologies and electromechanical devi ces (Housman et al, 2009;Huang and Krakauer, 2009;Backus et al, 2010;Mehrholz et al, 2012;Zariffa et al 2012). These devices allow time-specific tasks to be executed repeatedly in a controlled and reliable way, as this has been shown to be a determining factor in facilitating cortical reorganization, allowing a concomitant increase in motor ability and improved functional activity performance (Liepert, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the degree of motor function recovery after stroke is strongly related to the site and severity of the lesion, the recovery process may be stimulated and molded by rehabilitation programs using various techniques and exercises designed to promote motor relearning (Stein et al, 2007;Oujamaa et al, 2009). However, because of the limited success of traditional rehabilitation programs in restoring upper extremity function after stroke, researchers have been searching for other solutions, including ones integrating advanced technologies and electromechanical devi ces (Housman et al, 2009;Huang and Krakauer, 2009;Backus et al, 2010;Mehrholz et al, 2012;Zariffa et al 2012). These devices allow time-specific tasks to be executed repeatedly in a controlled and reliable way, as this has been shown to be a determining factor in facilitating cortical reorganization, allowing a concomitant increase in motor ability and improved functional activity performance (Liepert, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These devices allow time-specific tasks to be executed repeatedly in a controlled and reliable way, as this has been shown to be a determining factor in facilitating cortical reorganization, allowing a concomitant increase in motor ability and improved functional activity performance (Liepert, 2006). Recent evidence has shown that intensive repetition of movements could make a useful contribution to clinical practice (Kawahira et al, 2010), constituting a promising approach for patients affected by motor impairments due to neurological diseases, such as multiple sclerosis (Gijbels et al, 2011), cervical spinal cord injuries (Zariffa et al, 2012), and chronic stroke (Krebs et al, 2002;Macclellan et al, 2005;Sanchez et al, 2006;Masiero et al, 2007;Colombo et al, 2008;Kwakkel et al, 2008). Indeed, the use of devices designed to intensify therapy in the single patient could be a promising field of investigation (Masiero et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, persons with tetraplegia are provided with individually adapted aids and splints to make various skills easier. Any improvement of upper extremity function in individuals with tetraplegia is of major advantage.…”
Section: Introductionmentioning
confidence: 99%
“…The SCI participants included in the study showed a positive tendency towards a greater UEMS after the robotic training that did not reach statistical significance, possibly due to a deficient amount of robotic rehabilitation delivered (dose and duration, only 6-weeks of training), which may have been insufficient to produce a measurable change. The initial motor strength in the trained arm seemed to have no correlation with the degree of improvement in motor performance, as has been suggested by Zariffa and colleagues, when comparing robotic training with conventional therapy in subacute patients (Zariffa et al, 2012). Nevertheless, the presence of overall less spasticity in the group data at the beginning of the training showed the strongest correlation with the greater improvement in smoothness and aim.…”
Section: Discussionmentioning
confidence: 79%